Automotive model predictive control : models, methods and applications - Del Re, Luigi (Lecture notes in control and information sciences, 2010)
The proceedings of the Automotive Model Predictive Control: Models, Methods and Applications workshop investigates whether constrained predictive control is reasonable in automotive control and what is necessary for its application